Active concept in pedestrian design - Christianto Hendrawan; Yohanes Basuki Dwisusanto (ARTEKS : Jurnal Teknik Arsitektur, 2017)
In recent times, there’s an active living design trend in cities around the world, giving chances for people to actively move inside the city, making city healthier. Active Living can occur within pedestrian way along shopping street corridor which has potential to move shoppers from one store to another through walking. Pedestrian way along shop corridor are potentially attractive for people move around inside the city. The purpose of this study is to give us information about how far active living concept has been implemented within L. L. R. E. Martadinata street. The information and analysis can be use for further development in pedestrian way design. Our study conducted through analyzing existing active design problems along with literature studies about active living in design. Within the study, we conclude that L. L. R. E. Martadinata Street hasn’t quite well providing active living movement for shopping street pedestrian way. Pedestrian way has become uncomfortable, for people to walk from store to store within street corridor. There’s a missing value about active living, where people rather use automobile than actively moving along street corridor.